Some Lexical Aspects of Cape Muslim Afrikaans - Davids, Achmat (Lexikos, 1992)
It is a relatively well known fact that Cape Muslim Afrikaans has its own distinctive pronunciations which at times differ sharply with that of Standard Afrikaans. What is not so well known, is that apart from its core vocabulary, which is derived from Dutch, Cape Muslim Afrikaans also has a distinctive lexical inventory, created to essentially extend the limitations of the nineteenth century Cape Afrikaans. This essay looks at some aspects of that inventory. Retained within this distinctive lexical inventory are many lexical units which were discarded from Standard Afrikaans during the process of standardization. Cape Muslim Afrikaans also inherited some of its unique lexical units from the Malayo-Polynesian languages of the slave ancestors of the Cape Muslim community. While its vocabulary was further extended by borrowings from the languages of contact, English and French. Lexical items from Arabic came into its lexicon as a result of the translation of Arabic theological and theo-philosophical tracts into the Afrikaans mother tongue of this community. This essay looks at how the lexical inventory of Cape Muslim Afrikaans was disseminated and perpetuated in the Cape Muslim community. It looks at the role of the literary tradition of Arabic-Afrikaans and the Islamic religious education system at the Cape in this regard. Of particular interest are the changes which occur in the orthoepic nature and syntactical function of inherited and borrowed lexical units, by the affixing of lexical or grammatical morphemes, so that these units conform to the acoustic nature of Cape Muslim Afrikaans. The creation of composites and neologisms are also explored, while lists of inherited lexical units, with etymological origin, and more complex lexical items are provided. Keywords: cape muslim afrikaans, lexical aspects, core vocabulary, inherited and borrowed items, standard afrikaans, arabic afrikaans, arabic orthography, dutch, english, creolization, slave languages, religious education, neologisms, syntactical function, pronunciation, idioms and expressions